Production of biosurfactant from locally isolated bacteria - Rihab Hussein, Jawad (2010)
In this study, a total of 176 isolates was obtained from two coastal sampling locations. Out of this total, 124 (70.4%) isolates were obtained from the seawaters of the coast of Kertih, Terengganu while the remaining 52 isolates (29.5 %) were from Kuantan, Pahang. Five bacterial strains previously isolated were selected for the screening of biosurfactant producer(s) via three different characterization tests for biosurfactant; (i) surface tension measurements, (ii) emulsification activity, and (iii) cetyltrimethylammonium bromide assay (CTAB) test. One isolate coded KRT-142 identified as Pseudomonas aeruginosa was chosen to be the best candidate for biosurfactant production. Biosurfactant productions by isolated bacteria were found to be growth-associated in all the conditions tested. Microbiological properties of strain KRT-142 were investigated. It was found that strain KRT-142 produces water soluble, greenish yellow fluorescent pigments on a nutrient agar plate. It is an aerobic, gram negative, straight rods, motile bacteria, and not surrounded by sheaths. Ethanol as a carbon source was found to support the highest growth (as measured by whole cell protein) followed by glycerol and glucose. Slight growth was also observed with crude oil. Decreasing growth was observed with tetradecane, 1-propanol, 1-butanol, sucrose and maltose. Ethanol yielded maximum biosurfactant production, reducing the surface tension to 43.3 mN/m. It was followed by glycerol, hexadecane and crude oil with surface tension reduction to 44.5, 49 and 53.5 mN/m, respectively. The highest emulsifying activity was 56% at 7h and 52.7% at 14h for ethanol. In the study of organic nitrogen sources, soytone supported the highest growth followed by peptone, meat extract, yeast extract, tryptone and casamino acid, Soytone yielded the highest biosurfactant production, followed by meat extract and tryptone. At the optimum conditions (35oC, 4% inoculum size, 100 rpm and pH 7.2), the surface tension reached a minimum of 30.76 mN/m, after 6h in the stationary growth phase. Stable and compact emulsification index (E24) was observed after 2h of cultivation, reaching a maximal value of 86% at 6h of incubation.